Medical Imaging 2007: Visualization and Image-Guided Procedures 2007
DOI: 10.1117/12.711117
|View full text |Cite
|
Sign up to set email alerts
|

Integrated visualization of multi-angle bioluminescence imaging and micro CT

Abstract: This paper explores new methods to visualize and fuse multi-2D bioluminescence imaging (BLI) data with structural imaging modalities such as micro CT and MR. A geometric, back-projection-based 3D reconstruction for superficial lesions from multi-2D BLI data is presented, enabling a coarse estimate of the 3D source envelopes from the multi-2D BLI data. Also, an intuitive 3D landmark selection is developed to enable fast BLI / CT registration. Three modes of fused BLI / CT visualization were developed: slice vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Therefore, BLI or FLI datasets are often combined (fused) with high-resolution diffuse light photographs and co-registered Micro-CT datasets. Although we earlier demonstrated that this improves visual data navigation (Kok et al, 2007), the localization of a particular structure of interest remains challenging if the structure of interest does not show sufficient contrast, for instance for abdominal organs in Micro-CT. An automated whole-body segmentation of the entire animal, including the skeleton, would therefore greatly facilitate data interpretation.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, BLI or FLI datasets are often combined (fused) with high-resolution diffuse light photographs and co-registered Micro-CT datasets. Although we earlier demonstrated that this improves visual data navigation (Kok et al, 2007), the localization of a particular structure of interest remains challenging if the structure of interest does not show sufficient contrast, for instance for abdominal organs in Micro-CT. An automated whole-body segmentation of the entire animal, including the skeleton, would therefore greatly facilitate data interpretation.…”
Section: Introductionmentioning
confidence: 98%
“…Figure 5 gives an example of multi-view BLI to CT registration; in addition the articulated atlas is fitted to the CT. This way, an integrated data exploration is achieved, where the lightsource outer envelope is coarsely approximated from the optical images for superficial lesions [20]. Anatomical context is provided by the fitted atlas.…”
Section: Fusion Of Heterogenous Image Datamentioning
confidence: 99%
“…We have demonstrated that in application related to metastatic bone disease, there is a clear benefit in combining 3D BLI with lCT. By integrating tomographic BLI data sets with lCT-images from the same animal, information about tumor location from the optical imaging with high resolution structural details on the skeleton for the lCT imaging could be acquired [72] (Fig. 3).…”
Section: Combining Optical Imaging With Ct and Mrimentioning
confidence: 99%